A framework for ecosystem service assessment using GIS interoperability standards. (September 2021) - Lacayo, Martin; Rodila, Denisa; Giuliani, Gregory; Lehmann, Anthony
Abstract: Ecosystem Services Web Services (ESWS) are new web-based approaches to quantifying the benefits that humans derive from nature. Specifically, ESWS are the application of open web standards to ecosystem service assessment to facilitate creation, iteration, and dissemination in a seamless way. This integration streamlines collaboration, automation, and curation, while providing an open interface through which novel advances can be incorporated. The approach creates a new level of interoperability through data provenance whereby each transition between processing steps employs standards that ensure cohesive workflows across models and platforms. This imparts a modularity that can be examined and extended at every step. Highlights: Ecosystem services (ES) are essential for human well-being. The reproducibility crisis in GIScience has implications for ES. Software interoperability can improve data provenance. Web services are used to create interoperable workflows.